2019
DOI: 10.1002/ppap.201800173
|View full text |Cite
|
Sign up to set email alerts
|

Application of plasma jet to the inhibition of the proliferation of hepatic malignant cells via reactive oxygen species generation

Abstract: In vitro treatment of hepatic malignant cells with plasma‐activated medium conjugated with gemcitabine was investigated with a He plasma jet generated by a two‐ring dielectric barrier discharge (DBD) reactor. The DBD reactor was operated by high‐voltage pulses of alternating polarity (frequency: 20 kHz; pulse width: 4 µs). The electron density of plasma plume was estimated to be 9×1012 to 10×1012 cm−3, and the jet temperature was around 36℃. The plasma jet exhibited the inhibitory effects on the growth of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The selective killing of cancer cells without damaging normal cells is the most important feature of these methods. Numerous studies showed that both CAP and PAM have a selective effect toward oral cancer, [16] hepatic cancer, [17,18] skin cancer, [19,20] glioblastoma, [21][22][23] breast cancer, [24,25] pancreatic cancer, [26,27] OC, [28,29] neuroblastoma, [30] prostate cancer, [31] head and neck cancer, [32] lung cancer, [33] osteosarcoma, [34] leukemia, [35,36] and colorectal cancer [37] cells.…”
mentioning
confidence: 99%
“…The selective killing of cancer cells without damaging normal cells is the most important feature of these methods. Numerous studies showed that both CAP and PAM have a selective effect toward oral cancer, [16] hepatic cancer, [17,18] skin cancer, [19,20] glioblastoma, [21][22][23] breast cancer, [24,25] pancreatic cancer, [26,27] OC, [28,29] neuroblastoma, [30] prostate cancer, [31] head and neck cancer, [32] lung cancer, [33] osteosarcoma, [34] leukemia, [35,36] and colorectal cancer [37] cells.…”
mentioning
confidence: 99%
“…The average electron density of the He plasma jet was estimated as the ratio of the equilibrium number of electrons in one voltage period to the corresponding consumed gas volume of He, as shown in equation (5), which is adapted from [47,48]. Generally, the current monitor measures current by electron flow in a wire; therefore, ions in the plasma bullets may be still accounted for electrical charge of the plasma bullets by this method.…”
Section: Effect Of Shielding Gases On Electron Density Of Plasma Jetmentioning
confidence: 99%
“…As a result, the jet temperature can be in the range of 30 °C-70 °C. Consequently, in case of required jet temperature is close the human body temperature (<40 °C) in order to avoid effects of temperature on cells during plasma treatment [50,51], large consumptions of noble gases are required in the case of without shielding gas [19,47].…”
Section: Comparison Of Noble Gas Consumption Between Plasma Jet Sourcesmentioning
confidence: 99%
“…Li et al [25] found that PAM highly increased the efficacy of the chemotherapeutic agent cisplatin on hepatocellular carcinoma with cancer stem cell characteristics. Nyguen et al [27] demonstrated that PAM combined with gemcitabine triggered the deaths of hepatic malignant cells via ROS generation.…”
Section: Introductionmentioning
confidence: 99%